Translation and psychometric testing of the Farsi version of the Seattle angina questionnaire - Zahra Taheri-Kharameh (Health and Quality of Life Outcomes, 2017)
Abstract Background Angina pectoris causes substantial psychological and functional disabilities and adversely effects quality of life in patients. The aim of this study was to investigate the psychometric properties including validity and reliability of the Farsi version of the Seattle angina questionnaire. Methods The ‘forward-backward’ procedure was applied to translate this questionnaire from English to Farsi. The translated version of the Seattle angina questionnaire was assessed in terms of validity and reliability with a convenience sample of 200 patients suffering from angina pectoris who were recruited from the inpatient ward (post CCU) and outpatient department at two teaching hospitals in an urban area of Iran. Validity was assessed using content, face and construct validity. The calculation of the Cronbach’s alpha coefficient and the test-retest method helped with the assessment of reliability of the questionnaire’s five subscales. Construct validity of the questionnaire was evaluated using exploratory factor analysis. Results The results of exploratory factor analysis indicated a five-factor solution for the questionnaire including ‘physical limitation in middle to strenuous activities’, ‘physical limitation in slight activities’, ‘angina pattern and discomfort of treatment’, ‘treatment satisfaction’ and ‘disease perception’ that jointly accounted for 64.42% of variance observed. Convergent validity was mostly supported by the pattern of association between the Seattle angina questionnaire-Farsi version and the SF-36. Cronbach’s alpha of the subscales ranged from 0.60 to 0.86 and test-retest scores ranged from 0.79 to 0.97 indicating a good range of reliability. Conclusions The Seattle angina questionnaire-Farsi version had acceptable psychometric properties. Therefore, it can be used to assess health-related quality of life and assess the effects of different medical and nursing interventions on patients’ quality of life.